Use of Tropospheric Delay in GNSS-Based Climate Monitoring—A Review - Aleksandra Maciejewska (Remote Sensing)
The troposphere is a key component of the Earth’s climate system, modulating weather patterns and global temperatures through intricate interactions between water vapor, atmospheric pressure, and temperature. Nevertheless, the effective long-term monitoring of tropospheric variations continues to represent a significant challenge in the realm of climate science. While conventional methods such as radiosondes and satellite observations yield valuable data, they frequently face constraints related to temporal resolution, spatial coverage, or weather-dependent variations. In recent years, Global Navigation Satellite System (GNSS) meteorology has emerged as a promising alternative, offering continuous, high-precision atmospheric measurements. The objective of this review is to assess the application of GNSS tropospheric components in climate monitoring. Specifically, the following objectives are pursued: (1) examine how GNSS-derived ZTD, ZWD, and IWV reflect climate variability and long-term trends; (2) compare GNSS-based climate measurements with reanalysis and satellite datasets; (3) discuss the challenges and limitations of using GNSS for climate studies; (4) highlight future developments, including multi-GNSS integration and AI-driven climate data analysis.